Reluctant Privatization - Bernardo Bortolotti; Mara Faccio (Fondazione Eni Enrico Mattei (FEEM), 2004)
We study the evolution of the control structure of 141 privatized firms from OECD countries over the period from 1996 through 2000. We find that governments do not relinquish control after privatization. We show that the market-to-book ratios of privatized firms converge through time to those of a control sample. However, this convergence does not depend on whether governments relinquish their control rights. In fact, large government stakes have no negative effect on either adjusted market value or stock price performance.
Keywords: L33; D72; G15; H6; K22; 330; Privatization; Corporate governance; Corporate Governance; Privatisierung; OECD-Staaten